Competitive dominance in a secondary successional rain-forest community in Borneo - Davies, Stuart J.; Hardy, Semui (Cambridge University Press, 2006)
Competitive interactions among pioneer species may have a significant impact on the course of secondary succession in tropical rain forests. We predicted that the outcome of competitive interactions in early succession would vary with soil nutrient availability. To test this hypothesis we grew seven pioneer tree species alone and in dense competitive mixtures, with four nutrient treatments: no nutrient addition, and N, P, and N plus P addition. Performance of plants grown alone and in mixtures was strongly nutrient limited. However, contrary to expectation, the competitive hierarchy among the seven species was almost identical among the four nutrient treatments. The dominant species, Melastoma malabathricum, accounted for >70% of total stand biomass in all nutrient treatments. Seedlings of this species had higher rates of gas exchange and initial growth, and lower root allocation than the other species. Profiles of light availability within the competitive stands indicated that light levels at ground level were well above levels at which pioneer species can successfully survive and grow, yet seedlings of species other than Melastoma remained stunted. Leaf N concentrations in all stands were 25–55% reduced by competitive interactions, and N addition increased relative competitive performance in only Melastoma suggesting that Melastoma was particularly effective at N acquisition, limiting nutrient uptake by the other species. Toward the end of the experiment individuals of Melastoma began to reproduce, suggesting that the competitive hierarchy would have changed in a longer-duration experiment.